Influencing Factors of Students’ Use of New Media Teaching Classes on the Learning Attitude and Learning Satisfaction in Guangdong, China - Zhuo, Zhang (Scholar: Human Sciences, 2025)
Purpose: This study aims to explore the factors that influence the satisfaction and attitude of international trade students in Guangdong Province. The conceptual framework proposes causal relationships among teacher-student interaction, students’ autonomy, teachers’ technical readiness, perceived ease of use, interactivity, satisfaction, and attitude. Research Design, data, and methods: Using the quantitative method (N = 500), a questionnaire survey was conducted among sophomores and juniors majoring in international trade at Zhanjiang University of Science and Technology, Guangdong Province. The nonprobability sampling methods include judgmental, quota, and convenient sampling for collecting data. Structural equation modeling (SEM) and confirmatory factor analysis (CFA) were used to analyze the data, including model fit, reliability, and construct validity. Result: Teacher-student interaction, teacher technical preparation, and perceived usability significantly affected students’ learning satisfaction, and perceived usability and interaction affected students’ attitudes. However, student autonomy has no significant effect on students’ satisfaction with using new media. Conclusion: This study suggests that the management team and teachers of higher vocational colleges provide an assessment to measure the impact of new media classrooms on the development of higher vocational education to improve students’ satisfaction and attitude towards using new media classrooms.